Improving Family Health Through Education on Healthy Eating Patterns and Donating Herbal Drinks during the COVID-19 Pandemic - Atmadja, Taufiq Firdaus Alghifari; A'yunin, Nur Arifah Qurota; Indrianeu, Tineu; Susanti, Yeti; Utami, Nurul Mega; Hadi, Zahra Tazkianisa (LPPM Univ. Ibn Khaldun Bogor, 2022)
Indonesia is one of the countries experiencing the Covid-19 pandemic. One of the efforts to overcome the health problems caused by the pandemic is to pay attention to a healthy diet and equipped with supplements from herbal drinks that can boost the body's immune system. Based on the results of the analysis of the situation in the linggasirna and Jayaputra villages, information was obtained that the community has not understood the implementation of a healthy diet as one of the prevention of Covid-19 transmission and the lack of educational activities about Covid-19 prevention efforts. Providing education to PKK mothers who act as mediators of family health information in the community is expected to be the first step in solving the problem. Education of healthy eating patterns and herbal drinks is delivered using power point media. The positive response of participants to educational activities was seen from the activeness of participants during the discussion. Based on the results of pre-test and post-test data processing amounting to 10 multiple choice questions, the n-gain value obtained by PKK mothers of Linggasirna and Jayaputra villages is 6.3% and 7.1%. This shows that there is an increased understanding of PKK mothers before and after education